Formulation of Development Strategy of Public Accountant, A Case on KAP D & BCS Semarang - VM Budi Cahyo Santoso; Maria Yosephine Dwi Hayu Agustini; Thomas Indradaja (Journal of Management and Business Environment (JMBE), 2024)
This study aims to formulate an appropriate strategy for developing KAP D BCS using the Quantitative Strategic Planning Matrix (QSPM). The quantitative data in the form of the number of Public Accountants (AP) and Public Accounting Firms (KAP) obtained from the Directory of Public Accounting Firms and Public Accountants during 2010–2022, as well as literature studies. The qualitative data were obtained through observation, interview, and questionnaires. The data was analyzed using EFE Matrix, IFE Matrix, SWOT Matrix Diagram, TOWS Matrix, and QSPM. The analysis of the IFE and EFE matrixes respectively resulted in the total score of 0.63 and 0.08 which indicate aggressive strategy in particularly development strategy in the IE matrix. The assessment using QSPM ended up with innovation strategy that provides the highest total attractiveness value. The KAP can utilize information technology to support the process in providing assurance and non-assurance services, such as digitizing audit working papers (KKP), audit programs and procedures, training and library of the audit materials enabling them to be accessed from any place, and developing websites and digitizing HR data.